The Variation of Javanese Islamic Society in the Existence of Paranormal - M Dimyati Huda (Journal of Development Research, 2017)
Before some great religions come to Indonesia, there are some religion assured such as animism, dynamism. It trusted by Javanese until now. So that, they come to the paranormal to solve their problems. That ability is opposite with the syariat of Islam. Based on it, the most important problem should be investigated is the society of Islam who come to the paranormal, their belief that this is part of Javanese Islamic society in solving the problem and changing social life. The purpose of this study is to analyze variance Javanese Islamic society in its alteration and development in existence of Paranormal in traditional and modern life. This study was done in Sumberingin, Sanankulon, Blitar, East Java. The object of this study is to Paranormal ability. The Islamic society life is influenced by the traditional Java belief taught by their great-grandparents so that the myth of the invisible power of human can influence social life. There are three kinds of religion variation such as Islam Abangan and Islam Santri, yet Santri divided into young generation and old generation that in this study categories into Modern Santri and Traditional Santri